Maternal Outcome of Prolonged Pregnancy - Akhter, Parul; Sultana, Masuda; Hoque, Mahbuba; Sultata, Sharmin; Khatun, Mst Rahima; Dabee, Seema Rani (Journal of Bangladesh College of Physicians and Surgeons, 2015)
The probability of a pregnancy terminating in a full-term, healthy live birth is a powerful indicator of the health status of its women, and of the quality of health care available to them during pregnancy and birth. The present study conducted to find out the maternal outcome of prolonged pregnancy. This study carried out in the department of obstetrics, Sir Salimullah Medical College and Mitford Hospital, Dhaka, between the period of February 2003 and December 2003. Patients admitted in labour ward having the history of post dates but not in labour and some were admitted during first stage of labour. Patients who were sure about their Last Menstrual Period (LMP) and those patients who had regular menstrual cycle were included in the study. Total 139 respondents were included in the study. Among them 114 (82.01%) were in the age group of 18 to 29 years and 25 (17.99%) were in the age group of ?30 years. Among the respondents 67 (48.2%) were primi gravida and 72 (51.8%) were multi gravida. Among the respondents 92 (66.2%) were in the 1st stage of labour, 7 (5.0%) were in the 2nd stage of labour and rest 40 (28.8%) were not in labour. Mode of delivery of highest number of respondents was caesarian section (54.0%) followed by normal vaginal delivery (39.7%). Other mode of delivery were ventouse and forceps and they were 07(05.0%) and 2(1.4%) respectively. Out of 75 respondents under gone caesarian section, indication of C/S was fetal distress in 1st stage of labour, prolong 1st stage with maternal distress, failed induction, cephalopelvic disproportion (CPD) and breech presentation with big baby were 32.0%, 25.3%, 24.0%, 16.0% and 2.7% respectively. Maternal morbidity like PPH, UTI, puerperal sepsis and wound infection were 10.0%, 14.40%, 3.60% and 5.70% respectively. In postdated pregnancy maternal morbidity is common finding. It also has more operative interference. J Bangladesh Coll Phys Surg 2014; 32: 66-70